The Importance Of Statistical Evaluation In The Management Of The National Tourism Network (Eurasian Journal of Humanities and Social Sciences, 2025)
This article describes the role of tourism in the national economy, the factors influencing its development, improving the quality of services, issues and directions of statistical assessment of economic development in tourism.